Performance assessment to measure creativity through STREAM approach - Tri Wahyu Agustina; Maratus Sholikha; Asrianty Mas’ud; Nisa Sholehah Pangsuma (University of Muhammadiyah Malang, 2022)
Learning online during pandemic COVID-19 must still accommodate creativity. This study aimed to identify the level of student creativity using the STREAM (Science-Technology-Religion-Engineering-Arts-Mathematics) approach. It was conducted on an online practicum in the Plant Anatomy course. The purpose of this study was to identify the level of student creativity in various indicators of creativity through a performance assessment of the product of the practicum report. The static-group comparison design was used as the research design. The target population is the fourth-semester student in the Department of Biology Education. The samples were chosen using purposive sampling, determining class IV-A (39 students) as a regular class and class IV-C (38 students) as intervention one. The research was equipped with creativity performance tasks, rubrics with a scoring of practicum reports' performance assessments, and field notes. Each student designs and makes one of the anatomical structural models of roots, stems, or leaves. The practicum report was used to identify their level of creativity. The data were analyzed by calculating the creativity level percentage in a qualitative descriptive manner. The results showed that the creativity level of the intervention class is excelling (57.89%), while the regular class the emerging (58.79%). The STREAM approach provides a better level of creativity.